2017
DOI: 10.1016/j.rpor.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Siemens TT-D carbon fiber table top on beam attenuation, and build up region of 6 MV photon beam

Abstract: Despite providing minimal attenuation for the primary radiation, the assumption that carbon fiber couches are radiotranslucent is not valid, and the effects of couches of this type on the transmission factor, and on the skin dose should be carefully investigated for each field size and depth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For example, Seppälä et al 4 measured that the increased percentage of relative skin dose with involvement of eight different CFCs varied from 73.86 to 180.11% under the context of field size 10 cm × 10 cm for 6 MV photon, the best ones were Varian grid insert and Qfix kVue DoseMax which were both grid-based, those of most solid CFCs were similar to our data. For some counterparts, the surface dose effect in our work showed apparent superiority, for instance, David et al 24 measured that the increased skin dose with involvement of the iBEAM evo CFC was 513%, and Sheykhoo et al 25 reported their data of 514.53% increased skin dose with the 550 TXT CFC under the same context of 10 cm × 10 cm for 6 MV photon, while that of uRT- linac 506c was 213.25%. The effect depends on multiple factors including couch design and structure, material, photon beam quality, and field size as well.…”
Section: Discussionmentioning
confidence: 52%
“…For example, Seppälä et al 4 measured that the increased percentage of relative skin dose with involvement of eight different CFCs varied from 73.86 to 180.11% under the context of field size 10 cm × 10 cm for 6 MV photon, the best ones were Varian grid insert and Qfix kVue DoseMax which were both grid-based, those of most solid CFCs were similar to our data. For some counterparts, the surface dose effect in our work showed apparent superiority, for instance, David et al 24 measured that the increased skin dose with involvement of the iBEAM evo CFC was 513%, and Sheykhoo et al 25 reported their data of 514.53% increased skin dose with the 550 TXT CFC under the same context of 10 cm × 10 cm for 6 MV photon, while that of uRT- linac 506c was 213.25%. The effect depends on multiple factors including couch design and structure, material, photon beam quality, and field size as well.…”
Section: Discussionmentioning
confidence: 52%
“…There are several reports evaluating the validation of treatment couches modelling in TPS. 8,9,[17][18][19] In a study by Njeh et al, 8 the BrainLAB couch top has been modelled in Philips Pinnacle and BrainLAB iPlan RT Dose TPSs. They demonstrated an excellent agreement (1% for all gantry angles measured except for 120 o , which was 1•8%) between the measured dose and Pinnacle TPS computed dose using 6 MV photon beams.…”
Section: Discussionmentioning
confidence: 99%
“…The TC is made up of two thin carbon fiber plates that are about 2.0 mm to 4.0 mm thick and sandwich air-equivalent polymeric foam between them. And it contains a low attenuation property, high mechanical strength, rigidity, low density and lightweight in order to use in radiotherapy treatments (Olch et al, 2014;Sheykhoo et al, 2017). The immobilization devices such as Vac lok Cushions (VLC), All in One positioning system (AIO-PS) and thermoplastic mask are employed to ensure patient positioning during the course of the treatment.…”
Section: A Study To Analyze Impact Of Treatment Couch and Immobilizat...mentioning
confidence: 99%